Association between general and abdominal obesity with high blood pressure: difference between genders - Alison O. Silva; Micaelly V. Silva; Lisley K.N. Pereira; Wallacy M.N. Feitosa; Raphael M. Ritti-Dias; Paula R.B. Diniz; Luciano M.F.T. Oliveira (Elsevier, 2016)
Objective: To assess the association between general and abdominal obesity with high blood pressure in adolescents of both genders from the public school system. Methods: This was an epidemiological, descriptive, exploratory study, with a quantitative approach and local scope whose sample consisted of 481 high school students (aged 14-19), selected by using a random cluster sampling strategy. Blood pressure was measured through the use of automated monitor and was considered high when the pressure values were at or above the 95th percentile. The analyses were performed using the chi-squared test and binary logistic regression. Results: The prevalence of high blood pressure was 6.4%, and it was higher among boys (9.0% vs. 4.7%, p < 0.05). There was no significant difference between general (p = 0.903) and abdominal obesity (p = 0.157) when genders were compared. After adjusting for age, high blood pressure was associated with general (OR = 6.4; p < 0.001) and abdominal obesity (OR = 7.0; p < 0.001) only among boys, when comparing the fourth quartile with the first quartile of body mass index (≤18.6 kg/m2 vs. ≥23.5 kg/m2) and waist circumference (≤69 cm vs. ≥80.1 cm). Conclusion: It was observed that general and abdominal obesity are associated with high blood pressure only in boys, regardless of age. Resumo: Objetivo: Analisar a associação entre obesidade geral e abdominal com a pressão arterial elevada em adolescentes de ambos os gêneros da rede de ensino público. Métodos: Trata-se de um estudo epidemiológico, descritivo, exploratório, com abordagem quantitativa e abrangência municipal cuja amostra foi constituída de 481 estudantes (14-19 anos) do ensino médio, selecionado por meio de uma estratégia de amostragem aleatória de cluster. A pressão arterial foi medida através da utilização de equipamentos automáticos, sendo considerada elevada quando os valores pressóricos estivessem iguais ou acima do percentil 95. As análises foram realizadas através do teste de Qui-quadrado e da regressão logística binária. Resultados: A prevalência de pressão arterial elevada foi de 6,4%, sendo maior entre os rapazes (9,0% vs. 4,7%, p < 0,05). Não foi observada diferença significante entre a obesidade geral (p = 0,903) e abdominal (p = 0,157) quando comparados os gêneros. Após o juste pela idade, a pressão arterial elevada foi associada com a obesidade geral (OR = 6,4; p < 0,001) e abdominal (OR = 7,0; p < 0,001) apenas entre os rapazes, quando comparado o quarto quartil com o primeiro quartil do índice de massa corporal (≤ 18,6 Kg/m2 Vs ≥23,5 Kg/m2) e da circunferência da cintura (≤ 69 cm Vs ≥80,1 cm). Conclusão: Foi observado que a obesidade geral e abdominal está associada com a pressão arterial elevada apenas entre os rapazes, independentemente da idade. Keywords: Hypertension, Adolescent, Prevalence, Palavras-chave: Hipertensão, Adolescente, Prevalência